Agroecologia: um caminho para a Complexidade no ensino de Biologia no Ensino Médio - Ismerim, Julia de Camargo (Universidade Federal de São Carlos, 2025)
Edgar Morin's Complexity Theory perceives the universe in a holistic and interde- pendent way. Since agroecology is a science of Complexity, which combines contemporary scientific knowledge with traditional knowledge from rural and indigenous communities, with social, cultural, ethical and environmental principles, it allows the exploration of biological sciences in high school in a way that does not isolate their knowledge and allows the understanding of natural sciences and their interconnections with culture and society in a systemic way. To evaluate the biology teaching-learning process, this research involved theoretical and practical activities during a school year of Biology for a 3rd year high school class in Sorocaba-SP, with the objective of analyzing the use of agroecological practices and theoretical foundations of agroecology in the field of Complexity, as a reference in classes; a pedagogical visit was made to the Agroecological Learning Space at UFSCar-So, where students participated in practices of planting and managing agroecological gardens, with explanations about each stage. To evaluate the results of these activities, carried out in an integrated manner with Biology classes, the following were analyzed: initial perceptions of the students, informative materials produced by them, reflective essays and Biology tests. The results analyzed in this work, considering the increasing sophistication in the student’s writing, showed that agroecology can be an effective educational reference to broaden student’s understanding of nature and interactions between its elements and helped in the significant learning of the programmatic contents, especially Ecology, in the Biology discipline.
Agroecology: a path towards Complexity in the teaching of Biology in High School
Keywords: Complexidade; Agroecologia; Ensino de Biologia; Complexity; Agroecology; Biology teaching; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM